Molecularly Imprinted Polymers Modified by Deep Eutectic Solvents and Ionic Liquids with Two Templates for the Simultaneous Solid-Phase Extraction of Fucoidan and Laminarin from Marine Kelp. (11th February 2019) - Li, Guizhen; Dai, Yunliang; Wang, Xiaoqin; Row, KyungHo
Abstract: Molecularly imprinted polymers modified by deep eutectic solvents and ionic liquids (ILs) were prepared as packing materials for the solid-phase extraction (SPE) of fucoidan and laminarin. The prepared materials were characterized by field emission scanning electron microscopy and Fourier transform infrared spectroscopy. The polymers modified by the deep eutectic solvent prepared by choline chloride and urea had the best extraction efficiencies for fucoidan and laminarin (95.5% and 87.6%, respectively) from marine kelp. The relative standard deviations for intraday and interday determination were less than 4.23%. The molecularly imprinted polymers modified by deep eutectic solvents and ILs showed outstanding applications for SPE and may offer novel sample pretreatment for other analytes.